Oswajanie śmierci w wybranych wierszach współczesnych poetów - Władysława Bryła (Język. Religia. Tożsamość, 2023)
The author attempts to answer the question whether it is possible to think about death without fear. On the basis of poems by Wisława Szymborska, Elżbieta Skorupska-Raczyńska and Karol Wojtyla, she concludes that the death of the closest people is accompanied by grief and longing and it can be consoled by faith in God. In overcoming the fear of one’s own death a few things can be helpful, namely thinking about the inevitability of death, believing in life after death and leading a good life. Yet, mass death and the death of children cannot be tamed.